Qualitative Modeling of Spatial Orientation Processes using Logical Propositions: Interconnecting Spatial Presence, Spatial Updating, Piloting, and Spatial Cognition - Riecke, B. E.; Heyde, M. von der (Max Planck Institute for Biological Cybernetics, 2002)
In this paper, we introduce first steps towards a logically consistent framework describing and relating items concerning the phenomena of spatial orientation processes, namely spatial presence, spatial updating, piloting, and spatial cognition. Spatial presence can for this purpose be seen as the consistent feeling of being in a specific spatial context, and intuitively knowing where one is with respect to the immediate surround. The core idea of the framework is to model spatial orientation-related issues by analyzing their logical and functional relations. This is done by determining necessary and/or sufficient conditions between related items like spatial presence, spatial orientation, and spatial updating. This eventually leads to a set of necessary prerequisites and sufficient conditions for those items. More specifically, the logical structure of our framework suggests novel ways of quantifying spatial presence and spatial updating. Furthermore, it allows to disambiguate between two complementing types of automatic spatial updating: On the one hand, the well-known continuous spatial updating induced by continuous movement information. On the other hand, a novel type of discontinuous, teleport-like “instantaneous spatial updating” that allows participants to quickly adopt the reference frame of a new location without any explicit motion cues. ACKNOWLEDGEMENTS: This research was funded by the Max-Planck Society and the Deutsche Forschungsgemeinschaft (SFB 550 Erkennen, Lokalisieren, Handeln: neurokognitive Mechanismen und ihre Flexibilität).
Keywords: MPI-TR; Riecke; Riecke_2002; TR; bernhard-riecke; iSpaceWeb; markus-von-der-heyde; spatial updating